22. THE STUTUS OF PATIENT CARE AFTER INTERVENTIONAL TREATMENT FOR URETERAL STONES AT TUYEN QUANG PROVINCIAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: The stutus of patient care after interventional treatment for ureteral stones and related factors at Tuyen Quang provincial General Hospital in 2025.Subjects and methods: A prospective descriptive study was conducted on 107 patients from February to June 2025.Results: Most patients (91.6%) received satisfactory care, while only 8.4% received unsatisfactory care. Patients with a single stone received better care from nurses compared to those with two stones. Patients with a urinary catheter retention time of less than 24 hours after intervention received better nursing care than those with catheter retention time over 48 hours (p < 0.05).Conclusion: Nursing care was rated good in daily patient monitoring and evaluation activities; however, more attention is needed for patients with multiple stones and those with urinary catheter retention time exceeding 48 hours after intervention.
Keywords: Ureteral stone treatment, post-intervention.